Detection by PCR of Culicoides insignis Lutz (Diptera: Ceratopogonidae), the main vector of bluetongue virus (BTV) in the Neotropical region - Ayala, Mahia Mariel (2022)
Bluetongue Virus (BTV) cause a viral, non contagiosus disease that mainly affects sheep, cattle and wild and farmed ruminants causing damage to these animals and significant economic losses. It is well known in Central America and the Caribbean, and even in the Lesser Antilles, and in South America this virus has been isolated in Brazil, Argentina, Peru, Ecuador and Guyana. Culicoides insignis Lutz, the major BTV vector in South America, is one of the most frequent and abundant species found in Southeastern USA, the Caribbean Basin, and Central and South America, that is primarily associated with cattle farms. Accurate identification of biting midges is essential for the understanding of disease epidemiology and vector control.